2010
DOI: 10.1007/s10488-010-0319-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Implementation Research: Conceptual Distinctions, Measurement Challenges, and Research Agenda

Abstract: An unresolved issue in the field of implementation research is how to conceptualize and evaluate successful implementation. This paper advances the concept of “implementation outcomes” distinct from service system and clinical treatment outcomes. This paper proposes a heuristic, working “taxonomy” of eight conceptually distinct implementation outcomes—acceptability, adoption, appropriateness, feasibility, fidelity, implementation cost, penetration, and sustainability—along with their nominal definitions. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
6,145
3
48

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 4,898 publications
(6,562 citation statements)
references
References 54 publications
36
6,145
3
48
Order By: Relevance
“…The 5 implementation outcomes identified by Chaudoir et al10 based on a study by Proctor et al9 defined implementation outcomes as “the effects of deliberate and purposive actions to implement new treatments, practices, and services.”10 (p65) Two of the main functions of implementation outcomes are to serve as indicators of implementation success and key intermediate outcomes 9. For illustration, we defined the 5 implementation outcomes as they relate to the DPA evaluation.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…The 5 implementation outcomes identified by Chaudoir et al10 based on a study by Proctor et al9 defined implementation outcomes as “the effects of deliberate and purposive actions to implement new treatments, practices, and services.”10 (p65) Two of the main functions of implementation outcomes are to serve as indicators of implementation success and key intermediate outcomes 9. For illustration, we defined the 5 implementation outcomes as they relate to the DPA evaluation.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Studies have shown that there are multiple approaches to measuring implementation outcomes including self‐report surveys, observation, and use of archival records archival 7, 9, 10. Proctor et al9 found that developing implementation outcome measures that would be useful in real world settings are needed.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations